Pengampunan: Penerapan Prinsip-Prinsip Alkitabiah dari Ajaran Yesus dalam Membangun Hubungan dengan Tuhan dan Sesama - Asih Rachmani Endang Sumiwi; Joseph Christ Santo; Gabriel Levi Thusiapratama (Sekolah Tinggi Teologi Transformasi Indonesia, 2022)
Abstract: One of the Bible principles that Jesus taught is forgiveness. The teaching of forgiveness becomes a normative command if it is not accompanied by an applicative explanation. With a descriptive qualitative approach, the author systematically describes the practical application of forgiveness. This study came to the conclusion that forgiveness is an act of accepting and making peace with the person or situation that caused it. The reason for forgiveness is that because a believer has been reconciled to God, he should also live at peace with others. Forgiveness is an active decision to rebuild a relationship that has been damaged, and thus forgiving people is the same as solving problems. Christians must have the willingness to forgive without limits: without being limited in the frequency of mistakes, without being limited in time, and without being limited in the magnitude of the mistakes. Forgiveness has an impact on oneself and in relationships with God and others.Keyword: Forgiveness, Make Peace, Impact of ForgivenessAbstrak: Salah satu prinsip Alkitab yang diajarkan Yesus adalah hal mengampuni. Ajaran tentang pengampunan menjadi sebuah perintah normatif bila tidak disertai penjelasan aplikatif. Dengan pendekatan kualitatif deskriptif, penulis memaparkan secara sistematis aplikasi praktis dari mengampuni. Penelitian ini sampai pada kesimpulan bahwa mengampuni adalah tindakan menerima dan berdamai dengan orang atau keadaan yang menjadi penyebabnya. Alasan mengampuni adalah karena orang percaya telah diperdamaikan dengan Allah semestinya ia juga hidup berdamai dengan sesama. Mengampuni merupakan suatu keputusan aktif membangun kembali hubungan yang sudah rusak, dan dengan demikian orang yang mengampuni sama dengan menyelesaikan persoalan. Orang Kristen harus memiliki kerelaan untuk mengampuni tanpa batas: tanpa dibatasi frekuensi kesalahan, tanpa dibatasi jangka waktu, dan tanpa dibatasi besarnya kesalahan. Pengampunan memberikan dampak bagi diri sendiri maupun dalam relasi dengan Tuhan dan sesama.Kata Kunci: Mengampuni, Berdamai, Dampak Pengampunan